Development of Teaching Materials for Introduction to Geometry Based on Ethnomathematics for Grade II Elementary School Students - Arifani, Puan; Jesi Alexander Alim; Guslinda (Education Generation Journal, 2024)
This study aims to develop ethnomathematics-based teaching materials for introductory geometry material in grade 2 of Elementary School using the Plomp model (2013). The development stage is carried out using three stages, namely the Preliminary Research Stage, the Prototyping Stage, and the Assessment Stage. The teaching materials that have been developed are validated by three experts consisting of material experts, language experts and media experts. While practicality is seen from the questionnaire responses obtained from teachers and students. The data for this study were collected by means of observation, interviews and questionnaires. Data processing in this study was carried out by means of quantitative and qualitative analysis. The results of this study obtained Ethnomathematics-based teaching materials for introductory geometry material were stated to be very valid with an average percentage of 93.33%, and the product was stated to be very practical with an average percentage of 94%. So it can be concluded that the Ethnomathematics-based teaching materials for introductory geometry material that have been developed are valid and practical and can be used in learning.